Delayed diagnosis of annular pancreas in 11-year-old girl with DiGeorge syndrome - Mary Margaret Barr; James Gilbert; Zaria Murrell (Elsevier, 2020)
DiGeorge Syndrome is a collection of symptoms stemming from a heterozygous microdeletion on chromosome 22. An eleven-year-old girl with DiGeorge syndrome presented to our Pediatric Surgery with a history of episodes of vomiting since birth, and a recent hospitalization for aspiration pneumonia. Upper GI series demonstrated a large, distended stomach and duodenum with delayed passage of contrast into distal bowel.The patient had recurrent non-bilious emesis, throughout infancy and childhood. Over time, she adjusted her diet to primarily eat sauces and other soft foods, avoiding meat entirely. While being evaluated for recent aspiration pneumonia following emesis, a dilated duodenum and stomach was found on upper GI series, and she was referred to Pediatric Surgery. Originally suspecting a fenestrated duodenal web, it was discovered during surgery that the obstruction was caused by an annular pancreas. The obstruction was treated by a duodeno-duodenostomy using diamond anastomosis. By two-week follow-up, the patient advanced to a mechanical soft diet and tolerated full liquids well.Most annular pancreas patients present with complete obstruction in infancy. This patient presented with moderate symptoms in early adolescence. DiGeorge syndrome is loosely associated with various GI malformations, but annular pancreas has not been reported elsewhere in medical literature.